Flood Hazard Zonation and Agricultural Vulnerability Assessment Using GIS in Indonesia - A. St. Fatmawaty (CV. HEI PUBLISHING INDONESIA, 2025)
Riau Province, a low-lying region dominated by peatlands and high rainfall, is highly susceptible to severe flooding, posing significant risks to its key agricultural sectors (oil palm and rice). This study seeks to delineate flood risk and agricultural susceptibility by amalgamating Geographic Information Systems (GIS) with Multi-Criteria Analysis (MCA). Flood hazard zonation was generated using weighted physical parameters—Digital Elevation Model (DEM), rainfall, soil type, land cover, and river proximity—processed through the Analytical Hierarchy Process (AHP). Agricultural vulnerability was assessed using exposure, sensitivity, and adaptive capacity indicators derived from 2020–2025 secondary data. The results reveal that 18.5% of Riau Province falls under high-hazard zones, predominantly in Indragiri Hilir and Indragiri Hulu. Rice and oil palm in Indragiri Hilir were found to be the most vulnerable commodities, with an estimated annual economic loss of 350 billion Rupiah [11]. The resulting spatial maps provide essential guidance for the Riau Provincial Government in designing targeted mitigation measures, risk-based spatial planning, and improved agricultural adaptation strategies.